Os grandes empreendedores alagoanos. - Silva, Lavynia Maria Alves; Moreira, Caroline Oliveira; Le Campion, Ramon Lima; Soares, Ana Vitória Garcia; Mendes, João Victor Alves; Peixoto, João Victor Tenório Cavalcante; de Alencar, Gabriel Canuto (SEMPESq - Semana de Pesquisa da Unit - Alagoas, 2020)
Os grandes empreendedores alagoanos.